ON THE UNIFORMLY CONVERGENCE SPECTRAL EXPANSIONS CONNECTED WITH SCHRÖDINGER’S OPERATOR OF CONTINUOUS FUNCTIONS IN A CLOSED DOMAIN - Rakhimov, A. A.; Zakaria, K.; Khan, N. A. (The Nucleus, 2010)
Present paper is devoted to study summability problem of spectral expansions in a closed domain. We consider here as a spectral expansions eigenfunction expansions connected with one Schrodinger’s operator with singular potential in two dimensional domains with smooth boundary